PENERIMAAN VAKSINASI COVID-19 PADA MAHASISWA DI UNIVERSITAS CENDERAWASIH - Amin, Annisa Rizky Ananda; Assa, Inriyanti; Bouway, Dolfinus Yufu; Pariaribo, Konstantina; Adimuntja, Natalia Paskawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
COVID-19 vaccination aims to reduce COVID-19 transmission and reduce morbidity and mortality and achieve herd immunity in the community. This study is expected to determine the factors associated with vaccination acceptance in students at Cenderawasih University based on the theory of Health Belief Model. This study is analytic quantitative with cross sectional study design, using proportionated stratified random sampling technique, as many as 100 respondents in three faculties, namely FKM (26 people), FISIP (41 people), and FT (33 people). A questionnaire was used as the measuring instrument. The chi-square test was used to analyse this study’s univariate and bivariate data with 95% confidence level. The result of this study showed the majority of respondents 89 people had received COVID-19 vaccination, with high perceived susceptibility (59%), high perceived severity (64%), high health motivation (64%), perceived benefits (51%), and low perceived barriers (54%). There was a relationship between perceived benefits (p = 0,047; PR = 1,177; 95% = CI 1,019-1,359) and perceived barriers (p = 0,027; PR = 0,835; 95% = CI 0,718-0,972) with COVID-19 acceptance in students at Cenderawasih University. There was no relationship between perceived susceptibility (p = 0,756; PR = 1,023; 95% = CI 0,887-1,180), perceived severity (p = 0,196; PR = 1,106; 95% CI = 0,940-1,302) and health motivation (p = 0,196; PR = 1,106; 95% CI = 0,940-1,302) with the COVID-19 acceptance in student at Cenderawasih University. Factors influencing acceptance of COVID-19 vaccination for Cenderawasih University students are perceived benefits anf perceived barriers. Keywords: COVID-19, Vaccination, Health Belief Model, Students